The modified Glasgow prognostic score serves as a robust predictor of unplanned readmission and 1-year mortality in lung cancer patients receiving immune checkpoint inhibitors - Xue, Fengwang; Lu, Ruoqing; Wang, Cailian; Xiong, Qilian; Liu, Ying; Guo, Shengmin; Deng, Bo (Frontiers in Oncology, 2026)
BackgroundThe modified Glasgow Prognostic Score (mGPS), which reflects the degree of systemic inflammation and nutritional status, is associated with prognosis in various common malignancies. However, its association with 30-day unplanned readmission and 1-year mortality in stage III-IV lung cancer (LC) patients remains unvalidated. This study aimed to evaluate the prognostic value of mGPS in stage III-IV LC patients receiving immune checkpoint inhibitors (ICIs).MethodsIn this retrospective study, 209 patients diagnosed with stage III-IV LC who underwent ICI therapy between January 2023 and May 2024 were included. Patients were stratified based on mGPS scores into three risk categories: low-risk (0 points), intermediate-risk (1 point), and high-risk (2 points). Kaplan-Meier analyses, multivariate Cox proportional hazard regression, and subgroup analyses were employed to assess primary outcomes.ResultsAmong the enrolled patients, the rates of 30-day unplanned readmission and 1-year mortality were 35.4% (74/209) and 11.0% (23/209), respectively. Kaplan-Meier analysis indicated significantly elevated cumulative incidences of 30-day unplanned readmission and 1-year mortality in the high-risk group relative to intermediate- and low-risk groups (log-rank p < 0.001). Adjusted multivariable Cox regression revealed that each 1-point increase in mGPS conferred a 72% higher risk of 30-day unplanned readmission (HR 1.72, 95%CI 1.25-2.38, p = 0.001) and a 117% higher risk of 1-year mortality (HR 2.17, 95%CI 1.15-4.10, p = 0.017). Additionally, compared with low-risk patients, those in the high-risk group experienced a 198% increase in the risk of 30-day unplanned readmission (HR 2.98, 95% CI 1.56-5.69, p = 0.001) and a 366% increase in 1-year mortality risk (HR 4.66, 95% CI 1.33-16.35, p = 0.017). Trend tests confirmed that the risk of adverse outcomes rose steadily with increasing mGPS risk category. Subgroup analyses demonstrated that the prognostic effect of mGPS was consistent across age, TNM stage, metastatic status, and nutritional condition (p for interaction > 0.05).ConclusionHigher mGPS scores significantly correlate with elevated risks of both 30-day unplanned readmission and 1-year mortality among LC patients receiving ICI therapy. Routine mGPS monitoring may warrants further evaluation in prospective multicenter validation studies to inform prophylactic interventions.